Hodnocení finanční situace podniku - Palacký, Miloslav (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Bakalářská práce je zaměřena na finanční situaci podniku STAMEDOP a.s. za období od roku 2006 až 2008. Na základě zjištění problémových částí jsou formulovány návrhy opatření na zlepšení finanční situace současného stavu podniku. Práce je rozdělena na dvě části a to teoretickou a praktickou.

Bachelor thesis focuses on the financial situation of company STAMEDOP a.s.among the period from 2006 to 2008. Based on the findings problematic parts,there are formulated proposals for innovation to improve the financial situation of the current bussines state. The thesis is divided into two parts repectively methodological and practical.
The Evaluation of the Financial Situation’s Company
Keywords: Finanční analýza; horizontální analýza; vertikální analýza; elementární metody; rozvaha; výkaz zisku a ztrát; rozdílové ukazatele; poměrové ukazatele; Altmanův index; Index důvěryhodnosti českého podniku; Financial analysis; horizontal analysis; vertical analysis; elementary methods; balance sheet; profit and loss account; the differential indicators; ratios; Altman index; index of credibility of the Czech company